Feeding the Late and Moderately Preterm Infant: A Position Paper of the European Society for Paediatric Gastroenterology, Hepatology and Nutrition Committee on Nutrition. Issue 2 (August 2019) - Lapillonne, Alexandre; Bronsky, Jiri; Campoy, Cristina; Embleton, Nicholas; Fewtrell, Mary; Fidler Mis, Nataša; Gerasimidis, Konstantinos; Hojsak, Iva; Hulst, Jessie; Indrio, Flavia; Molgaard, Christian; Moltu, Sissel Jennifer; et al.
Abstract : ABSTRACT: Nutritional guidelines and requirements for late or moderately preterm (LMPT) infants are notably absent, although they represent the largest population of preterm infants. The European Society for Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) Committee on Nutrition (CoN) performed a review of the literature with the aim to provide guidance on how to feed infants born LMPT, and identify gaps in the literature and research priorities. Only limited data from controlled trials are available. Late preterm infants have unique, often unrecognized, vulnerabilities that predispose them to high rates of nutritionally related morbidity and hospital readmissions. They frequently have feeding difficulties that delay hospital discharge, and poorer rates of breastfeeding initiation and duration compared with term infants. This review also identified that moderately preterm infants frequently exhibit postnatal growth restriction. The ESPGHAN CoN strongly endorses breast milk as the preferred method of feeding LMPT infants and also emphasizes that mothers of LMPT infants should receive qualified, extended lactation support, and frequent follow-up. Individualized feeding plans should be promoted. Hospital discharge should be delayed until LMPT infants have a safe discharge plan that takes into account local situation and resources. In the LMPT population, the need for active nutritional support increases with lower gestational ages. There may be a role for enhanced nutritional support including the use of human milk fortifier, enriched formula, parenteral nutrition, and/or additional supplements, depending on factors, such as gestational age, birth weight, and significant comorbidities. Further research is needed to assess the benefits (improved nutrient intakes) versus risks (interruption of breast-feeding) of providing nutrient-enrichment to the LMPT infant.